PENGGUNAAN BENTUK TSUMORI DA DAN KI DA SEBAGAI MODALITAS MAKSUD DALAM BAHASA JEPANG - Desi Wildasari; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research analyze the differences uses tsumori da and ki da as modalities of intention in Japanese, and how tsumori da and ki da are used when subtituted. The purpose of this research is to understand about the differences using tsumori da and ki da as modalities of intention in Japanese. Data for analyzing taken from www.kotonoha.gr.jp/shonagon/. The used methods in this research is descriptive with the theory of modality. Technique used in analyzing data in the research that is by using substitution. The conclusion of analyzed data tsumori da and ki da exchangeable, but not all of them can be replaced, depending on which persona is using tsumori da and ki da.Keyword: Modality